The edition of the Statutes of the Florentine Republic of 1355 in vernacular, edited by Federigo Bambi, Francesco Salvestrini and Lorenzo Tanzini (Italian Review of Legal History, 2023)
With an elegant three-volume package, Leo S. Olschki Editore of Florence published in 2023 Gli Statuti della Repubblica Fiorentina del 1355 in vernacular, edited by Federigo Bambi, Francesco Salvestrini and Lorenzo Tanzini, filling a prolonged gap, already denounced by many historians. The edition has been promoted by the Deputazione di storia patria per la Toscana chaired by Giuliano Pinto, who notes in the foreword how it promises to be a valuable research tool for medievalists and legal historians, linguists, paleographers, diplomatists and art historians. The 1355 statutes are presented with a double draft: that of the “Statute of the Podestà” and that of the “Statute of the Captain of the People.” They were drafted at the behest of the Signoria, that is, the Priorato delle Arti and Gonfaloniere di Giustizia, that is, the apex of the city’s public order. Because of their great bulk and the difficulties of transcribing them from the vernacular in which the surviving copy was written, it required a long-drawn-out work begun in 1999 by Francesco Salvestrini, who was joined in later years by Lorenzo Tanzini, and Federigo Bambi. From the meticulous work of the three editors came their introductory essays that, with different approaches, offer perspectives indispensable to understanding the many meanings of the enactment. Salvestrini took care to place it in the historical and political context of which it was consequent and to probe its motivations and outcomes. Tanzini paid particular attention to the analysis of the internal dynamics of the Florentine legislation, tracing its premises and separating the actual novelties from the legacies of earlier regulations. To Federigo Bambi we owe a timely and refined study of legal language in the vernacular and the differentiation between the vulgarizer of the Statuto del Podestà and that of the Capitano, accompanied by the compilation in the third volume of a rich and useful glossary. Contributing to the further prominence of the text of the Florentine statutes is the date of 1355, which is a few years after the plague, in the middle of the century, when the Florentine commune increased its territorial expansion (Prato, Pistoia), taking further steps toward a regional state and giving the promulgation a significance wider than the city sphere. The Statutes of 1355 were a reflection of internal and external evolutions leading to the consolidation of a municipal bureaucracy and continued to be consulted thanks to an alphabetically ordered thematic repertory in the late 14th and early 15th centuries. All this was underpinned by a renewed civic awareness based on the pride of one’s history and the city’s political identity that drew from Guelphism and republican ideals against all seigniorial temptations. Vulgarization went in the same direction by increasing the value of the Statute as a reflection of a local and shared identity. Historiographic investigations of this body of statutes have long focused on archival, codicological and paleographic analysis while maintaining an eminently formal connotation. Recent contributions by Andrea Zorzi and Lorenzo Tanzini, have led to an organic analysis of the codices and their evolution in the political framework and in studies of the history of Florence, placing the application of the norms in the transformation of the system of government. The decision to publish the 1355 codices in the vernacular was dictated by the intent to make the broadest fourteenth-century Florentine statute writing usable, making available to scholars texts of particular relevance from a historical-legal, linguistic and philological point of view. The result is a better knowledge of fourteenth-century Florence with multiple references to institutional arrangement, participation in public life, and all aspects of everyday life. This edition acquires great cultural value by offering access to conspicuous witnesses to the affirmation of the vernacular even in public documents.
Keywords: medieval statutes; regulatory revisions; vigor and meanings of statutes; Florence in the fourteenth century; ernacular translations of Latin legal texts; glossary of words in the Florentine vernacular